Identification of phenyldibenzothiophenes in coals and the effects of thermal maturity on their distributions based on geochemical data and theoretical calculations. (December 2019) - Zhu, Zhili; Li, Meijun; Tang, Youjun; Qi, Ling; Leng, Junying; Liu, Xiaoqiang; Xiao, Hong
Highlights: All four phenyldibenzothiophene isomers are unequivocally identified in coals. The thermodynamic stabilities and geometric optimizations of PhDBTs were calculated. Two maturity indicators of PhDBTs for highly mature geological samples are proposed. The distributions of PhDBTs and MDBTs were compared. The origins of the phenyldibenzothiophenes in coals are discussed. Abstract: All four phenyldibenzothiophene (PhDBT) isomers were unequivocally identified in coals for the first time by the co-injection of authentic standards and comparison of the retention indices with those reported in previous studies. Based on density functional theory (DFT) calculations, the relative thermodynamic stability order of the phenyldibenzothiophene isomers (PhDBTs) was determined to be 3-PhDBT > 2-PhDBT > 4-PhDBT > 1-PhDBT. All PhDBT isomers were observed in a suite of coals from the Junggar and Ordos basins, and the effects of thermal maturity on their distributions were systematically investigated. Based on geochemical data and theoretical calculations, two phenyldibenzothiophene maturity indicators, i.e., PhDR1 (2-PhDBT/4-PhDBT) and PhDR2 ((2-PhDBT + 3-PhDBT)/4-PhDBT), are proposed. For high maturity coals (≥0.96 %Ro), PhDR1 and PhDR2 increase gradually with increasing thermal maturity. Two preliminary calibrations of these parameters against measured %Ro were made: %Rc = 0.60 × PhDR1 + 1.00 (≥1.00 %Ro) and %Rc = 0.30 × PhDR2 + 1.00 (≥1.00 %Ro). Compared to their corresponding methylated counterparts, phenyldibenzothiophenes are particularly useful as molecular markers of maturity at higher levels of thermal stress and provide a molecular assessment for sedimentary rocks containing types II and III kerogens where few biomarker parameters are available. PhDBTs in coals are likely to be generated during diagenesis/catagenesis as intermediate products in the formation of more condensed heterocyclic polycyclic aromatic compounds, such as triphenyleno[1, 12- bcd ]thiophene and benzobisbenzothiophenes, which were detected in the highly mature samples. This study broadens the current understanding of the occurrence, distribution, geochemical significance, and origin of phenyldibenzothiophenes in sedimentary organic matter.